Table of contents and introductory materials for Vol. 19, no. 1, Spring 2011 - Bruce Quantic (The Advocate, 2011)
This content includes the table of contents, editorial information, a message from the president of ATE-K, and a message from the editor for vol. 19, no. 1 (Spring 2011) for The Advocate.